Names of animals as the main unit of linguacultural (on the basis of Arab and Kazakh comparisons) - Ashraf, M. A.; Yeskentayeva, R. S. (Journal of Oriental Studies, 2016)
The article is devoted to the problem of portable zoonyms values describing the rights in the Arab and Kazakh. We investigate linguistic-cultural aspects of the comparative speed with the use zoonyms in two languages. Showing different values zoonyms that appear when compared with the human animal. Reveal cultural similarities and differences in the metaphorical use of the same names of animals analyzed in two languages, and the extent of the similarities or differences. Such an analysis will be of interest to specialists in the field of linguistics, comparative linguistics.